Activated Platelets and Platelet-Derived Extracellular Vesicles Mediate COVID-19-Associated Immunothrombosis - Ebeyer-Masotta, Marie; Eichhorn, Tanja; Weiss, René; Lauková, Lucia; Weber, Viktoria (Frontiers in Cell and Developmental Biology, 2022)
Activated platelets and platelet-derived extracellular vesicles have emerged as central players in thromboembolic complications associated with severe coronavirus disease 2019 (COVID-19). Platelets bridge hemostatic, inflammatory, and immune responses by their ability to sense pathogens via various pattern recognition receptors, and they respond to infection through a diverse repertoire of mechanisms. Dysregulated platelet activation, however, can lead to immunothrombosis, a simultaneous overactivation of blood coagulation and the innate immune response. Mediators released by activated platelets in response to infection, such as antimicrobial peptides, high mobility group box 1 protein, platelet factor 4 (PF4), and PF4+ extracellular vesicles promote neutrophil activation, resulting in the release of neutrophil extracellular traps and histones. Many of the factors released during platelet and neutrophil activation are positively charged and interact with endogenous heparan sulfate or exogenously administered heparin via electrostatic interactions or via specific binding sites. Here, we review the current state of knowledge regarding the involvement of platelets and platelet-derived EVs in the pathogenesis of immunothrombosis, and we discuss the potential of extracorporeal therapies using adsorbents functionalized with heparin to deplete platelet-derived and neutrophil-derived mediators of immunothrombosis.